Bishops' identities, careers, and networks in medieval Europe - Bishops' Identities, Careers and Networks Conference; Thomas, Sarah E. (Medieval church studies, 2021)
Bishops were powerful individuals who had considerable spiritual, economic, and political power. They were not just religious leaders; they were important men who served kings and lords as advisers and even diplomats. They also controlled large territories and had significant incomes and people at their command. The nature of the international Church also meant that they travelled and had connections well beyond their home countries, were players on an increasingly international stage, and were key conduits for the transfer of ideas.00This volume examines the identities and networks of bishops in medieval Europe. The fifteen papers explore how senior clerics attained their bishoprics through their familial, social, and educational networks, their career paths, relationships with secular lords, and the papacy. It brings together research on bishops in central, southern, and northern Europe, by early career and established scholars. The first part features five case-studies of individual bishops? identities, careers, and networks. Then we turn to examine contact with the papacy and its role in three regions: northern Italy, the archbishopric of Split, and Sweden. Part III focuses on five main issues: royal patronage, reforming bishops, nepotism, social mobility, and public assemblies. Finally Part IV explores how episcopal networks in Poland, Sigüenza, and the Nidaros church province helped candidates achieve promotion. These contributions will thus enhance of our understanding of how bishops fit into the religious, political, social, and cultural fabrics of medieval Europe